In the Footsteps of Dante - Bartolomei, Teresa,Figueiredo, João R. (De Gruyter, 2023)
Dante, the pilgrim, is the image of an author who stubbornly looks ahead, seeking and building the
10.1515/9783110796049
Keywords: Alighieri; Dante; Christlicher Humanismus; Göttliche Komödie; Portugiesisch / Literatur